1993
DOI: 10.1073/pnas.90.21.10230
|View full text |Cite
|
Sign up to set email alerts
|

mu opiate receptor: cDNA cloning and expression.

Abstract: ABSTRACT,u opiate receptors recognize morphine with high affinity. A 2.1-kb rat brain cDNA whose predicted translation product displays 63% identity with recently described 8 and K opiate receptor sequences was identified through polymerase chain reaction and cDNA homology approaches. This cDNA recognizes a 10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
172
0
4

Year Published

1996
1996
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(189 citation statements)
references
References 60 publications
13
172
0
4
Order By: Relevance
“…1B), the secretion signal of the S. cerevisiae c~-mating factor was used to facilitate membrane translocation of the receptor. In both cases, part of the amino-terminus of the receptor was deleted since it has been reported that this had no effect on ligand binding [20][21][22]. DNA fragments comprising the fusion genes flanked by 5' and 3' AOX1 sequences were electro-transformed into the GSll5 (his4) and the protease-deficient SMDl168 (his4, pep4) P. pastoris strains and His + transformants were selected.…”
Section: Resultsmentioning
confidence: 99%
“…1B), the secretion signal of the S. cerevisiae c~-mating factor was used to facilitate membrane translocation of the receptor. In both cases, part of the amino-terminus of the receptor was deleted since it has been reported that this had no effect on ligand binding [20][21][22]. DNA fragments comprising the fusion genes flanked by 5' and 3' AOX1 sequences were electro-transformed into the GSll5 (his4) and the protease-deficient SMDl168 (his4, pep4) P. pastoris strains and His + transformants were selected.…”
Section: Resultsmentioning
confidence: 99%
“…Morphine acts at seven transmembrane domain, G proteinlinked receptor products of genes encoding , , and ␦ opiate receptor subtypes (1)(2)(3)(4)(5)(6)(7)(8)(9). Each of these genes is expressed in neurons in several neuronal circuits implicated in nociception (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…The -opioid receptor ( OR) is a seven-transmembrane domain, G protein-linked receptor that is a key member (Wang et al 1993), along with the enkephalinpreferring ␦ (Kieffer et al 1992) and dynorphin-preferring receptors (Minami et al 1993), of the constellation of brain receptors that recognize morphine and other opiate drugs (Uhl et al 1994). Pharmacologic approaches have suggested that the receptor, for which morphine has the highest affinity (Pasternak 1993), also serves as a principal site for morphine actions in inducing behavioral reward (Di Chiara and North 1992;Wise 1996), locomotion (Stevens et al 1986), analgesia (Porreca and Burks 1993), tolerance (Aghajanian 1978), and physical dependence (Johnson and Fleming 1989).…”
mentioning
confidence: 99%